Early work load tests for evaluation of long-term prognosis of acute myocardial infarction. Issue 7 (July 1977) - Granath, A; Södermark, T; Winge, T; Volpe, U; Zetterquist, S
Abstract : Exercise tests performed 3 and 9 weeks after acute myocardial infarction in 205 patients were found to give prognostic information on the survival during a follow-up period of 2 to 5 years. The appearance of tachycardia, major ventricular arrhythmias, or anginal complaints during these early exercise tests was thus accompanied by a significantly increased mortality during the observation period. Ventricular arrhythmias disclosed by exercise proved to be of higher prognostic significance than those recorded at rest on the same occasions. The usefulness of early exercise tests in the evaluation of the response to antiarrhythmic treatment after acute myocardial infarction as well as of the prognostic importance of the effects was documented in a smaller series of patients.